First we use sin(a+b)= sinacosb+sinbcosa
and cos(a+b)=cosa cosb -sinasinb
tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)
and sin(x+pi/2) = sinxcospi/2 + sinpi/2cosx =cosx,
<span>cos(x+pi/2) = cosxcospi/2- sinxsinpi/2= - sinx,
</span> because <span>cospi/2 =0, </span>and <span>sinpi/2=1
</span><span>=tan(x+pi/2)= sin(x+pi/2) / cos(x+pi/2)= cosx / -sinx = -1/tanx = -cotx
</span>from where <span>tan(x+pi/2)=-cotx</span>
Answer:
0.4077
Step-by-step explanation:
It's important to use parenthesis to avoid confusion.
9^(2x) = 6
Use exponent properties:
(9^2)^x = 6
81^x = 6
Take log of both sides
ln(81^x) = ln(6)
Use log properties:
x ln(81) = ln(6)
Solve for x:
x = ln(6) / ln(81)
x ≈ 0.4077
F(x)=2(3)-5
f(x)=6-5
f(x)=1
Answer:
correct anwer=27
Step-by-step explanation:
the anwer for this equation comes out to be 27. As simple as it becomes on applying paranthesis to this equation therefore we get
8+(30/2)+4=27
we need to apply the paranthesis using the method of BODMAS.
which favours division over addition.
therefore,correct anwer is 27 and not 13